Thermodynamic Study of the Solubility of Benzoin in Ethyl Acetate (1)+Ethanol (2) Mixtures (2023)
The equilibrium solubilities of benzoin (3) in ethyl acetate+ethanol mixtures were determined at several temperatures from 283.15-323.15 K. The Gibbs energy, enthalpy and entropy of solution and of mixing were obtained from these solubility data